2021
DOI: 10.3390/biom11030410
|View full text |Cite
|
Sign up to set email alerts
|

Actin-Resistant DNase1L2 as a Potential Therapeutics for CF Lung Disease

Abstract: In cystic fibrosis (CF), the accumulation of viscous lung secretions rich in DNA and actin is a major cause of chronic inflammation and recurrent infections leading to airway obstruction. Mucolytic therapy based on recombinant human DNase1 reduces CF mucus viscosity and promotes airway clearance. However, the marked susceptibility to actin inhibition of this enzyme prompts the research of alternative treatments that could overcome this limitation. Within the human DNase repertoire, DNase1L2 is ideally suited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 84 publications
3
9
0
Order By: Relevance
“…Dnase1L3 is naturally resistant to actin inhibition, in part, due to Phe-134 that disrupts the "central hydrophobic interface" with actin in Dnase1 12,25 . A similar mechanism of actin resistance was proposed for Dnase1L2 46 . Other determinants for actin resistance in Dnase1L3 include the disruption of stabilizing salt-bridged networks needed for actin binding to Dnase1, and the electrostatic repulsion of actin at the binding interface.…”
Section: Discussionsupporting
confidence: 59%
“…Dnase1L3 is naturally resistant to actin inhibition, in part, due to Phe-134 that disrupts the "central hydrophobic interface" with actin in Dnase1 12,25 . A similar mechanism of actin resistance was proposed for Dnase1L2 46 . Other determinants for actin resistance in Dnase1L3 include the disruption of stabilizing salt-bridged networks needed for actin binding to Dnase1, and the electrostatic repulsion of actin at the binding interface.…”
Section: Discussionsupporting
confidence: 59%
“…Recombinant Dnase1 is administered in CF patients to improve mucociliary clearance and pulmonary function [89][90][91]. Dnase1L2 is under development as a next-generation treatment for CF [92]. Beyond CF, Dnase1 has been tested in other pulmonary diseases, including asthma, obstructive pulmonary disease, chronic pulmonary diseases, and hemorrhagic shock [93][94][95].…”
Section: Clinical Applications Of Dnase1mentioning
confidence: 99%
“…As these macrophages were isolated from the lungs of cystic fibrosis-model mice, the authors suggested that macrophages were the target effector cells of the anti-inflammatory effects of vardenafil [ 95 ]. The pathogenesis and progression of cystic fibrosis are regulated by many factors, such as microbial infection, cytokines, enzymes, and gene mutations [ 94 , 96 , 97 , 98 ]. In addition, PDE5 can affect these pathogenic activities in cystic fibrosis in various organs in a macrophage-independent manner [ 94 , 95 , 99 , 100 ].…”
Section: Phosphodiesterase Type 5 Inhibitors and Macrophagesmentioning
confidence: 99%